The shrinkage behavior of boreholes drilled through deepwater creeping salt formations in West Africa - Wang, Mingchun; Deng, Jingen; Li, Zhong; Li, Mengbo; Xing, Zixiao; Zhang, Zhe; Yan, Chuanliang (Frontiers in Energy Research, 2024)
Salt formations, frequently encountered during oil and gas drilling, are very likely to form a complex underground environment, which are extremely harmful and have always been a particular concern in petroleum engineering industry. Under the geostress, salt rock generally shows obvious creep properties, which give rise to a certain risk to drilling. The creep and shrinkage of a wellbore drilled in Block B in West Africa were analyzed. Results show that after drilling the wellbore in the salt formation, the creep rates are different in the directions of two horizontal principal stresses on the wellbore wall: the creep rate is fastest (slowest) in the direction of the minimum (maximum) horizontal principal stress. The shrinkage rates in different directions tend to be same with time, and the wellbore shape changes from an ellipse to a circle. The higher the drilling fluid density is, the slower the wellbore shrinkage rate. The research results can provide theoretical guidance for selecting the drilling fluid density applied to salt formations.